Sistem Informasi Administrasi Sekolah Berbasis Web Pada MTs Daarul Falah - Alfi Nurshidqi; Shandi Noris (CV. Multi Kreasi Media, 2023)
The development of information technology today has provided great benefits for the world of education, the construction of school websites and the development of computer-based administrative information systems are examples of the use of information technology. Information technology allows administrative data to be processed quickly and easily so that in presenting reports the required administrative information can be obtained quickly, precisely, and efficiently. The purpose of this system is to overcome the old system that has been running at MTS Daarul Falah Karang tengah, Tangerang. With the implementation of the new system at MTS Daarul Falah Karang Tengah, Tangerang, it can increase the knowledge and abilities of staff, teachers and principals in the field of web-based administrative information system that will be entered into the system includes information about student data, subjects, student grades and student learning outcomes. And for the software used is a DBMS (Data Base Management System) which is used as a data storage medium in MySQL, the programming languages PHP, JavaScript, CSS, and HTML are used to create a website display that aims to make it easier for users and administrators to manipulate data.